Construction of Caco-2 cell hollow fiber bioreactor for the study on functional substances - XU Dongdong; CHU Qiang; YANG Yunyun; LÜ Xiangmin; ZHANG Yanzhen; ZHENG Xiaodong (浙江大学学报. 农业与生命科学版)
Human colon carcinoma cell line Caco-2 has been extensively used over the last thirty years as a model of the intestinal barrier. The parental cell line undergoes a process of spontaneous differentiation that leads to the formation of a monolayer of cells, expressing several morphological and functional characteristics of the mature enterocyte. Hollow fiber membrane bioreactors can offer an in vivo-like microenvironment for adherent cell types, such as Caco-2 cells, and enable a high quantity of the desired cellular product with less population variation and favorable operation costs.The objective of this study is to construct a novel Caco-2 cell hollow fiber membrane bioreactor, to explore the feasibility for further application by morphological observation and functional test of Caco-2 cells.In this experiment, the Caco-2 cells were cultured in polyethersulfone (PES) and polyvinylidenefluoride (PVDF) hollow fiber membranes as well as the classic Transwell culture plate. The morphological features of the cells were observed by optical microscope and scanning electron microscope (SEM), and the cell growth characters were examined by 3- (4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT). Meanwhile, the integrity of the cell monolayer was verified by fluorescence microscopy. The polarization and compactification of the monolayer was determined by brush border enzymatic activity, including the activities of alkaline phosphatase and γ-glutamyltransferase. In this way, the proliferation and differentiation of Caco-2 cells were compared and evaluated in three-dimensional hollow fiber bioreactor and two-dimensional models.Subsequently, time-dependent morphological observation of cell layers indicated that the Caco-2 cells cultured on hollow fiber, spread well and showed clear outline, and gradually formed confluent monolayer within 10 days. The brush border enzymes were well differentiated with higher expressed function within 8-14 days compared to the traditional model, and all of them tended to be consistent in the late cultivation.In conclusion, both the PES and PVDF hollow fiber membranes can effectively accelerate the proliferation and differentiation of Caco-2 cells during the 21-day culture period, resulting in the construction of a highly stable three-dimensional cell model. Eventually, the three-dimensional Caco-2 cell hollow fiber membrane bioreactors of PES and PVDF are successfully constructed, and the model has advantages over the traditional Transwell monolayer model.